Catholic, woman, mother, young: A pioneer in the Supreme Court - Legarre, Santiago (2023)
This short article is part of a larger project titled the Catholic Supreme Court Justices, which will include an intellectual biography of each and every Catholic Justice in the history of the Supreme Court of the United States. This segment is on Amy Coney Barrett. It first highlights her unusual choices in educational matters; next, it focuses on her family and her work. Regarding the latter, it analyzes both her short stint in the bench of the federal Court of Appeals and her even shorter one (at the time this contribution was penned) at the Supreme Court. It concludes that to understand correctly the relevance of the Catholicity of this Justice of the Supreme Court, one needs to understand the teachings of the Catholic Church on separation of Church and State (and of religion and law).